2016
DOI: 10.1093/rheumatology/kew246
|View full text |Cite
|
Sign up to set email alerts
|

Validation of disease activity indices using the 28 joint counts in systemic sclerosis

Abstract: All four disease activity composite indices were found to be valid measures for assessing arthritis in SSc. DAS28-ESR showed the best performance regarding reliability and construct validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…In a recent large multicentre prospective investigation of consecutive SSc cases ("DeSScipher" study) the prevalence of at least two tender and swollen joints of the hands was 10% of the 2162 enrolled cases (unpublished data). Our recent data also showed that tender/swollen joints were most often present in the metacarpophalangeal (MCP) line and wrist (40). Otherwise, occasionally temporomandibular joints may also be involved (41)(42)(43).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In a recent large multicentre prospective investigation of consecutive SSc cases ("DeSScipher" study) the prevalence of at least two tender and swollen joints of the hands was 10% of the 2162 enrolled cases (unpublished data). Our recent data also showed that tender/swollen joints were most often present in the metacarpophalangeal (MCP) line and wrist (40). Otherwise, occasionally temporomandibular joints may also be involved (41)(42)(43).…”
mentioning
confidence: 87%
“…We have recently validated the RA-related disease activity indices (DAIs) in SSc for truth, discrimination and feasibility (40). Seventy-seven patients with SSc, 40 RA patients, 20 patients with primary Raynaud's syndrome (PR), and 28 healthy volunteers were assessed.…”
mentioning
confidence: 99%
“…The reliability and validity of DAS28 have been established in previous studies. Cronbach's α of DAS28 coefficient ranged from 0.65–0.94 and test–retest reliability ranged from 0.85–0.92 (Leeb et al, ; Lóránd et al, ; Salaffi, Cimmino, Leardini, Gasparini, & Grassi, ; Uhlig, Kvien, & Pincus, ; Walsh et al, ). DAS28 was well‐correlated with health assessment questionnaire (HAQ) and disease activity score (DAS; Prevoo et al, ; Salaffi et al, ).…”
Section: The Studymentioning
confidence: 99%
“…18 The Disease Activity Score 28 using erythrocyte sedimentation rate (DAS28-ESR) and C-reactive protein (DAS28-CRP), the Simplified Disease Activity Index (SDAI) and the Clinical Disease Activity Index CDAI (all used in RA) have also been shown to be valid for SSc patients, with the DAS28-ESR showing the best performance regarding reliability and construct validity. 7 Joint involvement, specifically synovitis, is associated with elevated levels of acute phase reactants. 11 The responsiveness of erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) to change with respect to arthritis symptoms has not been specifically recognized in SSc.…”
Section: Assessing Arthritis In Sscmentioning
confidence: 99%
“…[4][5][6] Unfortunately, the treatment of arthritis in SSc has not yet been studied as a primary outcome in randomized controlled trials (RCTs), and arthritis-specific outcome measures for SSc have not been well validated. 7 Although the best strategies for managing arthritis in SSc have not yet been borne out by arthritis-specific RCTs, rheumatologists caring for patients with SSc must address this complaint regularly. In this review, we describe the spectrum of arthritis and discuss management considerations.…”
Section: Introductionmentioning
confidence: 99%